2020
DOI: 10.7717/peerj.9635
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of microbial communities among colonies and genotypes in nursery-reared Acropora cervicornis

Abstract: Background The architecturally important coral species Acropora cervicornis and A. palmata were historically common in the Caribbean, but have declined precipitously since the early 1980s. Substantial resources are currently being dedicated to coral gardening and the subsequent outplanting of asexually reproduced colonies of Acropora, activities that provide abundant biomass for both restoration efforts and for experimental studies to better understand the ecology of these critically endangered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 74 publications
(96 reference statements)
3
16
0
Order By: Relevance
“…These findings point to MD3-55 as the driving factor distinguishing genotype-specific epibiomes, similar to those signatures reported for A. cervicornis tissue samples (Klinges et al 2020;Miller et al 2020;Baker et al 2021). MD3-55 were previously visualized (Gignoux-Wolfsohn et al 2020), and are known to lack basic metabolic pathways, strongly supporting an intracellular lifestyle (Klinges et al 2019).…”
Section: Md3-55 In the Epibiomesupporting
confidence: 86%
“…These findings point to MD3-55 as the driving factor distinguishing genotype-specific epibiomes, similar to those signatures reported for A. cervicornis tissue samples (Klinges et al 2020;Miller et al 2020;Baker et al 2021). MD3-55 were previously visualized (Gignoux-Wolfsohn et al 2020), and are known to lack basic metabolic pathways, strongly supporting an intracellular lifestyle (Klinges et al 2019).…”
Section: Md3-55 In the Epibiomesupporting
confidence: 86%
“…Numerous studies have demonstrated the surprising dominance of the parasitic genus Aquarickettsia in microbiomes of A. cervicornis , and in particular, of disease-susceptible genets of this species (Shaver et al 2017 , Rosales et al 2019 , Klinges et al 2020 , Baker et al 2021 , Aguirre et al 2022 , Miller et al 2020 , Casas et al 2004 , Gignoux-Wolfsohn et al 2020 ). Results from this study were consistent with previous work, as populations of Aquarickettsia were found to comprise 74.98% of the microbiome in samples of A. cervicornis genotype 50, a disease-susceptible genotype (Muller et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous 16S ribosomal RNA (rRNA) amplicon-based studies have reported Endozoicomonas (Gammaproteobacteria)-affiliated taxa as the dominant members of the coral microbiome, with diverse phylotypes associated with individual species and across taxonomically dispersed hosts (11,(17)(18)(19)(20). Endozoicomonas strains have been isolated from corals, and their metabolic potential was inferred from derived genomic studies on the isolates and metagenomes assembled from culture-independent studies, suggesting integrated metabolic links facilitating nutrient acquisition and provision and therefore potentially important roles in host health (14,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%